Ribosome Rescue Pathways in Bacteria - Müller, Claudia; Crowe-McAuliffe, Caillan; Wilson, Daniel N. (Frontiers in Microbiology, 2021)
Ribosomes that become stalled on truncated or damaged mRNAs during protein synthesis must be rescued for the cell to survive. Bacteria have evolved a diverse array of rescue pathways to remove the stalled ribosomes from the aberrant mRNA and return them to the free pool of actively translating ribosomes. In addition, some of these pathways target the damaged mRNA and the incomplete nascent polypeptide chain for degradation. This review highlights the recent developments in our mechanistic understanding of bacterial ribosomal rescue systems, including trans-translation mediated by tmRNA and SmpB, ribosome rescue by the alternative rescue factors ArfA and ArfB, as well as BrfA, an additional rescue system found in some Gram-positive bacteria, such as Bacillus subtilis. Finally, we discuss the recent findings of ribosome-associated quality control (RQC) in particular bacterial lineages mediated by RqcH and RqcP. The importance of rescue pathways for bacterial survival suggests they may represent novel targets for the development of new antimicrobial agents against multi-drug resistant pathogenic bacteria.